THE USE OF FIGURATIVE LANGUAGE IN A HEAD FULL OF DREAMS ALBUM BY COLDPLAY - Cicih Nuraeni; Yunus Yunus; Akhmad Hairul Umam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
The purpose of this study is to investigate the types of figurative language, the most dominant, and the contextual meaning of figurative used in lyrics of Coldplay’s Album song entitled A Head Full of Dreams. The research uses a qualitative method that describes the analysis factually, accurately and systematically. Figurative language is a language that uses words or expressions with a meaning that is different from the literal interpretation. Based on research findings, there are six types of figurative language used in A Head Full of Dreams Album by Coldplay. They are hyperbole, metaphor, personification, simile, irony and symbol. Awhile the most dominant type of figurative language is hyperbole stated in 34 lyrics. So, the contextual meaning of A Head Full of Dreams Album by Coldplay is giving a lot of relationships, memories, and social lives. Keywords: figurative language, song, contextual meaning.